2022
DOI: 10.2147/idr.s373183
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 Vaccination Breakthrough Infections in a Real-World Setting: Using Community Reporters to Evaluate Vaccine Effectiveness

Abstract: Purpose Coronavirus disease 2019 (COVID-19) has highlighted the need for new methods of pharmacovigilance. Here, we use adult community volunteers to obtain systematic information on vaccine effectiveness and the nature and severity of breakthrough infections. Methods Between December 15, 2020 and September 16, 2021, 11,826 unpaid community-based volunteers reported the following information to an on-line registry: COVID-19 test results, vaccination (Pfizer, Moderna, or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previously published studies found that males are more likely to get infected [8] , [5] , [6] . Another study done in the United States found that females are more likely to get infected [7] , this can be due to the different baseline genetics, ethnicity and demographics of our population. In addition, we found that the incidence of COVID-19 breakthrough infection was higher in the 15–45 age group, and this is similar to what was reported in a study done in the United States that showed the average age of infection is 44.5 years old [7] .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previously published studies found that males are more likely to get infected [8] , [5] , [6] . Another study done in the United States found that females are more likely to get infected [7] , this can be due to the different baseline genetics, ethnicity and demographics of our population. In addition, we found that the incidence of COVID-19 breakthrough infection was higher in the 15–45 age group, and this is similar to what was reported in a study done in the United States that showed the average age of infection is 44.5 years old [7] .…”
Section: Discussionmentioning
confidence: 85%
“…Another study done in the United States found that females are more likely to get infected [7] , this can be due to the different baseline genetics, ethnicity and demographics of our population. In addition, we found that the incidence of COVID-19 breakthrough infection was higher in the 15–45 age group, and this is similar to what was reported in a study done in the United States that showed the average age of infection is 44.5 years old [7] . Reopening of schools and universities likely explains this finding, in addition to maintaining limited social activities for the older population.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This result supports earlier research demonstrating that vaccination offers considerable protection against the most severe COVID-19 disease signs as well as general infection protection. 10 To evaluate vaccine safety and surveillance, it is important to follow the fully vaccinated individuals to diagnose any serious complications or infections especially severe cases or dead people due to COVID-19 disease. According to the CDC report, a total of 10,262 SARS-CoV-2 vaccine breakthrough infections were diagnosed in 46 states of the United States until April 30, 2021; of those 160 (2%) cases have died.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is an essential component to build immunity against COVID‐19; however, evidence suggests immunity wanes over time, and booster doses are necessary for additional protection against severe acute respiratory syndrome‐coronavirus‐2 (SARS‐CoV‐2) infection and morbidity 1,2 . Follow‐up of vaccine trial participants and real‐world effectiveness studies 3,4 show a growing risk of breakthrough infection with greater time from initial vaccination 5 …”
Section: Introductionmentioning
confidence: 99%